Development of Underwater Observatory Systems for Monitoring Ocean Ecosystem - Arima, Masakazu; Tonai, Hirofumi; Kosuga, Yuki (2012 Fifth International Conference on Emerging Trends in Engineering and Technology, 2012)
The purpose of this research is to develop underwater observatory systems for monitoring ocean ecosystem. It is very important to protect the global ecosystem and to preserve biodiversity in the ocean. Recently, various kinds of underwater vehicles were actively involved in ocean research, i.e., seabed resources exploration, ocean environment monitoring. Underwater glider eSOARER', deep-sea video camera system, the Oceanic Radio-controlled Camera Approacher eORCA2' and an acoustic observatory system were developed for monitoring ocean ecosystem. SOARER has an ocean environmental sensors for monitoring depth, temperature, conductivity, salinity, DO, chlorophyll-a and turbidity. Ecology of marine organism living in a deep sea and marine mammals at sea surface can be recorded by using these devices effectively.